Convivendo com a morte e o morrer : o ser-enfermeiro em unidade de terapia intensiva - Sanches, Patricia Gisele (2007)
Interest in current study hails from my life work, my professional experience and the continuous contact with patients in the Intensive Care Unit (ICU). In their daily life at the ICU nurses live with the anguish experienced by patients and their relatives owing to the complexity of their physical and emotional state, especially imminent death, to the accomplishment of a great number of complex procedures and to intense work. Current research aims at understanding the manner nurses who work at ICUs experience the death process and patient's state of dying. The phenomenological research is adequate to recuperate the subjectivity of the experience while considering the subject in his/her existential dimension. The subjects of current research were nurses who signed the Term of Free Commitment and who work at the adult ICU of a school hospital in the northeastern region of the state of Paraná, Brazil. Data were collected through interviews recorded and transcribed wholly. The master question involved: What do the death and the dying of a patient in your care mean? After the interview has been transcribed, analysis followed according to Martins (1992). A close analysis of the interviews showed categories indicated by nurses, or rather, experiencing death and the dying of patients are processes that pervade the following issues: 1- The therapeutic obstinacy as a means in the process of death and dying. 2- The difficult living with a multiprofessional team and the process of death and dying. 3- Relationship with death. 4- The dynamics of work and its implications in the death and the dying of patients. 5- The relationship with the family of the patient who is in the process of dying. 6- The appeal for support within the death and dying processes. The most important thing is the fact that since many things have been said on quality living, dealing with death in daily life gives a higher value to the professionals in the context of living wholly and with quality above all. The difficulty of dealing with death, as a natural process of living, frequently helps the professional to make desperate attempts to keep alive patients known to be biologically dead. Discourse affirms that the death theme and the relationship with such patients should be more discussed in the university's curriculum so that the meaning of such phenomena may be demythologized from the idea of fear. A new form of understanding and sensitivity should be endeavored to deal with the death and dying processes. Only when professionals that work in health centers understand that death is part and parcel to existence, will they be able to bewith- the-patient in an authentic way during the latter's terminal period. They should also learn that death and dying are not always a challenge to be overcome but an inalienable part of life.